A new perspective of analysis in the labor process. The conclusion of the process for non-attendance at the hearings and the resumption of the limitation period - Torres Falcón, Thalia (2023)
The purpose of this paper is to evaluate the possibility of resuming the counting of the limitation period (Article 1997 of the Peruvian Civil Code), interrupted with the filing of the lawsuit, when the negligence of the plaintiff materializes in the labor judicial process and, specifically, when the process ends due to the non-attendance of the parties to the hearings scheduled in the first instance of the labor judicial process. It is proposed to carry out an analysis of interpretation –using the method of ratio legis for rules involved to verify whether the negligence described is comparable to abandonment of the process and, therefore, constitutes a case of ineffectiveness of the interruption of the limitation period.